Determinat factors influenced consumer’s decision: a study in a regional public hospital - Ruliyandari, Rochana; Hazerika, Nisrina (Intelektual Pustaka Media Utama, 2023)
Nowadays, there are lots of hospitals both managed by the private and public sectors. It is a fact that patients have an excellent opportunity to choose the hospital they want to be treated in, which will lead to higher competition between hospitals. Hospitals must be ready to compete with public and private hospitals. The strategy is carried out as well as possible for the success of the services offered by the hospital. One that can be done is using the 7Ps marketing mix theory (product, price, place, promotion, people, physical evidence, and process), which aims to increase the number of visits to the hospital. This research is quantitative research, descriptive-analytic with a cross-sectional approach. The sample size in this study was 110 people, chosen from outpatients in the studied hospital. The sampling technique in this study used purposive sampling with criteria determined by the researcher. The analysis used in this study is multivariate analysis. In this study, it was found that all variables influence consumer decision-making. However, from the seven variables that have been tested, three variables greatly influence consumer decisions partially in using services in the studied hospital. These variables are promotion, process, and physical evidence.